Educational Effectiveness, Efficiency, and Equity in Spanish Regions: What does PISA 2015 Reveal? - Francisco López Rupérez; Isabel García García; Eva Expósito-Casas (Karolinum Press, 2019)
The territorial organization of Spain into regions (autonomous communities) involves a remarkable decentralization. Therefore, it is interesting to make a comparative efficiency analysis of the public spending in education among regions that can to shed light on both the educational policies at the regional level, and the corrective state actions of inter-territorial imbalances. Furthermore, equity of the results of the education system is an indisputable goal of any society that aspires to justice and social cohesion. This research poses, firstly, an estimation of educational effectiveness and efficiency of public spending using a secondary analysis of PISA 2015 data that takes into account the value of ESCS. Subsequently, two educational equity parameters are estimated. The triple empirical categorization of autonomous communities, according to the efficiency and equity results, allows the derivation of policy recommendations of interest both at the regional and central government levels.